Pedagogical Content of Forming Tolerance on young people (Eurasian Scientific Herald, 2023)
In the article the rоle and to study Pedagogical Content of Forming Tolerance on young people is highlighted. As tolerance is not only a characteristic of a person's personality, but a social virtue, a set of qualities that regulate the relationships of all people, teach them to live in peace and harmony, alleviate conflicts between people and encourage them to compromise. This article is very relevant in explaining some points of that.